2021
DOI: 10.1177/1747021820982165
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in gaze behaviour during social interaction: An eye-tracking study with an embodied conversational agent

Abstract: Previous research has highlighted age-related differences in social perception, in particular emotional expression processing. To date, such studies have largely focused on approaches that use static emotional stimuli that the participant has to identify passively without the possibility of any interaction. In this study, we propose an interactive virtual environment to better address age-related variations in social and emotional perception. A group of 22 young (18–30 years) and 20 older (60–80 years) adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…This study used a Pepper social robot as main stimulus to initiate referential gaze. Previous research has showed an age-related decline in the perception of gaze from a virtual agent [ 25 ]. In this research, we extended this to a commercially available robot which is also lacking eye movement, contrary to a virtual agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study used a Pepper social robot as main stimulus to initiate referential gaze. Previous research has showed an age-related decline in the perception of gaze from a virtual agent [ 25 ]. In this research, we extended this to a commercially available robot which is also lacking eye movement, contrary to a virtual agent.…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive research on referential gaze in HRI (for two reviews on this, Ruhland et al [ 23 ] and Admoni & Scasellatti [ 24 ]), as well as research on gaze following in older adults (for a review, see Zafrani et al [ 8 ]). Nevertheless, to the best of our knowledge there is not published work involving both, with the notable exception of Pavic et al [ 25 ]. In this section, we will introduce these topics separately, as well as the use of online studies in HRI.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual Reality-based technologies are increasingly used in the field of healthcare and scientific research for simulating cognitive and socio-emotional skills (Riva and Serino, 2020) or studying human social interaction (Pan and Hamilton, 2018). Thus, it is now possible to interact and communicate with a virtual partner, such as embodied conversational agents (ECA) (Cassell et al, 2000;Loveys et al, 2020;Pavic et al, 2020), and thanks to the ability of ECAs to simulate and mimic human behavior, users tend to interact with them as with a real person (Gratch et al, 2013) and to assign them mental states (Callejas et al, 2014). In the context of healthcare simulation training, embodied VPs are typically computer-based programs using ECAs and simulating real patients and emulating a clinical encounter (see Cook and Table 1 | Overview of annotated attributes in our selected list of articles presented on Section 2.…”
Section: Role and Interest Of Embodied Virtual Patients In Healthcare...mentioning
confidence: 99%
“…For example, one study conducted by affective and reactive virtual agents showed that ocular strategies in social cognition for information gathering are different whether the experimental setting is interactive or not and whether healthy aging individuals listen or answer (Pavic et al, 2021) to the question asked by virtual avatars animated by a platform named "Virtual Interactive Behaviour" (Pecune et al, 2014). Another example Giraud et al (2021) present a design of a virtual interactive system in which a virtual agent plays a mediator role for the training of children with autism spectrum disorder (ASD).…”
Section: Virtual Agents Provide Interactionmentioning
confidence: 99%